Emotion Focused Coping in Single Mother Who has Adolescence with Autism - Dina, Elisabet Fransiska; Faizah, Faizah; Dara, Yuliezar Perwira (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
Single mother who has adolescence with autism have higher stress level than mothers who have normal ones and make themto do coping, one of them is emotion focused coping. The research is qualitative phenomenology based and analyzed with Miles Hubberman. Result showed most subjects tend to cope with escape (rejection and wishful thinking), social emotional support (family and environment), self control (patient), distancing (avoiding problems), positive reappraisal (pray to God) and accepting responsibility (acceptance and responsibility). Single mothers tend to cope with their own way frequently to reduce stress and when they facing their child behavior.